Low-temperature baking type PVC plastisol and preparation method thereof
By using low-temperature baking PVC plastisol, the synergistic effect of its components is used to solve the problems of slow curing speed, high baking temperature and unstable bonding strength of existing PVC plastisols, achieving high strength and rapid curing effect, and is suitable for bonding of various materials.
Patent Information
- Application Number
- CN202510385487.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-29
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-29
AI Technical Summary
The existing PVC plastisol has a slow curing speed, a high baking temperature, and the bonding strength needs to be improved. Especially when pasting metal materials such as aluminum and aluminum alloy surfaces, the bonding strength is unstable.
Low-temperature baking PVC plastisol is used, and its components include PVC paste resin, Copa resin, biphenyl epoxy resin, shea butter, dioctyl maleate, isopropyl myristate, PEG-10 distearate, calcium stearate, zinc stearate, nano calcium carbonate, M50 isocyanate curing agent, aziridine crosslinking agent, antioxidant, etc. The plastisol is prepared through a special preparation method, which has the characteristics of high bond strength and rapid low-temperature curing.
It realizes high-strength bonding between PVC materials and metal materials, has good high-temperature resistance and low-temperature stability, is suitable for bonding of various materials, and has a low baking temperature and fast curing speed.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a low-temperature baking type PVC plastisol and a preparation method thereof. Background Art
[0002] In the early stages of material application, the materials used in various industries were relatively single and the structures were relatively simple. With the development of society and the advancement of technology, various fields have put forward higher requirements for material performance, prompting people to continuously explore new materials and new processes to meet diversified needs.
[0003] Aluminum alloys are widely used in many fields due to their advantages such as light weight, high strength and good corrosion resistance. In the fields of aerospace, automobiles, etc., aluminum alloys are used to manufacture structural parts such as fuselages and interiors, effectively reducing weight and improving fuel efficiency and performance; in the field of construction, aluminum alloys are used in door and window frames, curtain walls, etc., which are not only beautiful and durable, but also can reduce the overall weight of buildings and improve energy-saving effects; in the field of electronic equipment manufacturing, aluminum alloys are often used to manufacture the shells of mobile phones, computers and other equipment, which can not only ensure the lightness and portability of the products, but also provide good heat dissipation performance and mechanical strength.
[0004] PVC molded parts play an important role in many fields due to their low cost, strong plasticity, good insulation and excellent appearance. In the field of home decoration, PVC is widely used to make floors, wallpapers, door and window seals, etc. Its rich color and texture selection can meet the needs of different decoration styles; in the electrical field, PVC is widely used as an insulating material in the outer sheath of wires and cables to ensure the safety of power transmission; in the field of toy manufacturing, PVC has become a common material for making various toys due to its good plasticity and cost advantages. PVC molded parts are widely used in automotive interior trims, exterior protective parts and some functional parts due to their low cost, strong plasticity, good insulation and excellent appearance.
[0005] In practical applications, the combination of different materials can give full play to their respective advantages and achieve better performance. However, the surface of aluminum alloy is smooth and easy to form a dense oxide film. As a high molecular polymer, PVC has difficulty in directly combining the two. Traditional mechanical connection methods, such as riveting and bolting, not only increase weight and damage the integrity of the material, but also may reduce the strength of components due to stress concentration, affecting the appearance and sealing performance of the product, and cannot meet the needs of various industries for lightweight products and overall performance improvement. Therefore, the development of a reliable and efficient connection method to achieve a firm bond between PVC molded parts and aluminum alloys has become a problem that many industries need to solve.
[0006] The product's use environment is complex and diverse, and the pasting process must ensure that the bonding between PVC and aluminum alloy is long-lasting and stable under various conditions. For example, in a hot and humid industrial environment, the pasting point cannot be detached to avoid equipment failure; in a cold outdoor environment, the adhesive cannot become brittle and lose its viscosity.
[0007] Early glue products faced many challenges when bonding PVC materials. Ordinary glues were difficult to form a strong enough chemical bond with the PVC surface, resulting in low bonding strength and easy debonding. At the same time, the surface energy of PVC materials is low, which makes the wettability of glue on its surface poor, affecting the penetration and adhesion of glue. In addition, PVC may be affected by environmental factors such as temperature, humidity, and ultraviolet rays during use, which requires the matching glue to have good weather resistance and durability.
[0008] In order to solve these problems, researchers began to explore adding PVC components to the glue, and PVC plastisol glue came into being. The principle of PVC plastisol glue is to use the principle of like dissolves like, so that the PVC components in the glue and the bonded PVC materials can better blend with each other. When the glue is applied to the PVC surface, the solvent will first swell the surface of the PVC material, and the PVC components in the glue will also be dissolved or dispersed. As the solvent evaporates, the glue gradually solidifies, and the PVC components and the bonded PVC materials are intertwined at the molecular level to form a tight connection, thereby significantly improving the bonding strength and stability.
[0009] In the process of formula development, in addition to PVC resin, a variety of auxiliary ingredients need to be added. For example, the addition of plasticizers can adjust the flexibility and plasticity of the glue, prevent the glue from cracking due to brittleness after curing, and also help improve the wettability of the glue to the PVC material; stabilizers can prevent PVC from being degraded due to heat, light and other factors during processing and use, ensuring the performance stability of the glue; the selection of solvents must consider both the solubility of PVC resin and other components, and also take into account factors such as volatility, toxicity and environmental protection, to ensure the operability of the glue during construction and safety after use; the use of fillers can adjust the physical properties of the glue, such as viscosity, hardness, etc., while also reducing costs.
[0010] With the continuous advancement of science and technology and the continuous improvement of product quality requirements in various industries, PVC plastisols are forced to continue to develop and improve. At present, PVC plastisols still have the following technical problems: (1) Slow curing speed: In some occasions where rapid assembly or construction is required, the curing speed of PVC glue cannot meet the requirements, resulting in reduced production efficiency or extended construction period; high-temperature baking at around 150°C is required to accelerate curing, but high-temperature baking will cause degradation and degeneration of the substrate, and the temperature will affect surrounding heat-sensitive devices.
[0011] (2) Low bonding strength: When the glue is applied to the PVC material surface, the bonding strength is relatively good, but when it is pasted to metal materials, such as aluminum and aluminum alloy surfaces, the bonding strength is uneven and generally needs to be improved.
[0012] Therefore, it is necessary to continuously develop the composition and production technology of glue to meet the requirements of more efficient and stable use. Summary of the invention
[0013] Aiming at the problems of slow curing speed, high baking temperature and need to improve the bonding strength of existing PVC plastisols, the present invention provides a low-temperature baking type PVC plastisol and a preparation method thereof. The PVC plastisol ingredients include PVC paste resin, Copal resin, biphenyl epoxy resin, shea butter, dioctyl maleate, isopropyl myristate, PEG-10 distearate, calcium stearate, zinc stearate, nano calcium carbonate, M50 isocyanate curing agent, aziridine crosslinking agent, antioxidant, etc. Each ingredient is prepared by a special preparation method to obtain a plastisol, which has good high and low temperature resistance, high bonding strength, and fast low-temperature curing. It is not only suitable for bonding PVC materials, but also suitable for bonding various metal materials. The specific technical scheme is as follows: A low-temperature baking type PVC plastisol comprises the following raw materials in parts by mass: 80 to 100 parts of PVC paste resin, 10 to 15 parts of Copal resin, 5 to 10 parts of biphenyl epoxy resin, 5 to 8 parts of shea butter, 25 to 35 parts of dioctyl maleate, 10 to 15 parts of isopropyl myristate, 3 to 5 parts of PEG-10 distearate, 2 to 4 parts of calcium stearate, 1 to 3 parts of zinc stearate, 10 to 20 parts of nano calcium carbonate, 2 to 3 parts of M50 isocyanate curing agent, 1 to 3 parts of aziridine crosslinking agent, 0.5 to 1 part of antioxidant 1010, 0.5 to 1 part of antioxidant 168, 0.1 to 0.3 parts of silicone defoaming agent, 3 to 5 parts of pigment and 15 to 25 parts of diluent.
[0014] In the above PVC plastisol, the PVC paste resin is a homopolymer resin with a degree of polymerization of 1000-1300.
[0015] In the above PVC plastisol, the particle size of the calcium stearate is sieved through 800-900 meshes.
[0016] In the above PVC plastisol, the particle size of the zinc stearate is sieved through 650-800 meshes.
[0017] In the above PVC plastisol, the particle size of the nano calcium carbonate is less than 100 nm.
[0018] In the above PVC plastisol, the pigment is at least one of titanium dioxide and graphite powder.
[0019] In the above PVC plastisol, the titanium dioxide is rutile titanium dioxide, and the particle size of the titanium dioxide is sieved through 325-500 meshes.
[0020] In the above PVC plastisol, the particle size of the graphite powder is sieved through 200-325 meshes.
[0021] In the above PVC plastisol, the diluent includes ethyl acetate.
[0022] The above-mentioned method for preparing a low-temperature baking type PVC plastisol comprises the following steps: S1: Add PVC paste resin to the reactor according to the mass fraction, stir at 300r / min~500r / min, add dioctyl maleate, stir at 25℃~32℃ for 15min~20min, then add isopropyl myristic acid and PEG-10 distearate, stir for 30min~45min, so that the PVC paste resin is fully swollen and mixed evenly to form a uniform basic glue solution; S2: Add 80% to 90% by mass of diluent, shea butter, Copal resin and biphenyl epoxy resin to the base glue solution, and stir at a speed of 300 r / min to 500 r / min to blend evenly; S3: Add calcium stearate, zinc stearate, nano calcium carbonate and pigment according to their mass proportions, stir at a speed of 500 r / min to 600 r / min, and mix evenly; S4: Add antioxidant 1010, antioxidant 168 and silicone defoamer according to their mass fractions, stir at a speed of 150r / min to 200r / min for 10min to 15min, let stand for 3min to 5min to allow bubbles to fully overflow, then add M50 isocyanate curing agent and aziridine crosslinking agent, stir at a speed of 200r / min to 250r / min, mix evenly and without bubble defects; S5: Finally, add the remaining diluent, stir at a speed of 150 r / min to 250 r / min, adjust the viscosity until it is uniform, and obtain PVC plastisol, which is sealed for storage.
[0023] In the above preparation method, the temperature does not exceed 32°C during the entire mixing process.
[0024] In S3 of the above preparation method, the calcium stearate, zinc stearate, nano calcium carbonate and pigment are uniformly mixed by double cone mixing or air flow mixing before being added.
[0025] In S2 of the above preparation method, the stirring time at a speed of 300 r / min to 500 r / min is 10 min to 20 min; the shea butter, copal resin and biphenyl epoxy resin are pre-mixed evenly with the diluent before being added.
[0026] In S3 of the above preparation method, the stirring time at a speed of 500 r / min to 600 r / min is 20 min to 30 min.
[0027] In S4 of the above preparation method, the stirring time at a rotation speed of 200 r / min to 250 r / min is 30 min to 45 min.
[0028] In S5 of the above preparation method, the stirring time at a rotation speed of 150 r / min to 250 r / min is 25 min to 30 min.
[0029] In the method for using the low-temperature baking type PVC plastisol, the coating amount of the PVC plastisol is controlled at 120 g / m² to 250 g / m², and the baking temperature is controlled at 65°C to 80°C.
[0030] The present invention provides a low-temperature baking type PVC plastisol and a preparation method thereof, and the beneficial effects are: 1. PVC paste resin is the main component, providing the basic polymer skeleton and determining the basic properties of the material. Copa resin improves the viscosity and flexibility of PVC plastisol, improves its adhesion to different materials, and helps to improve the chemical resistance of the material. Biphenyl epoxy resin enhances the cross-linking structure of PVC plastisol, improves the hardness, wear resistance and chemical corrosion resistance of the material, and makes the material more stable after curing. Shea butter plays a plasticizing role, increases the flexibility and ductility of the material, and can also improve the processing properties of the material, making it easier to apply and shape. Dioctyl maleate is mainly used as a plasticizer to reduce the hardness of PVC paste resin, improve flexibility, make the material softer, and reduce hardness and brittleness. Isopropyl myristate is an excellent solubilizer and lubricant that can improve the compatibility between the components and make the mixing more uniform. It also helps to improve the touch and gloss of the material. PEG-10 distearate has emulsifying and dispersing effects, which can prevent the agglomeration of the components and improve the stability of the system; it is also a plasticizer that enhances the flexibility of the material. Calcium stearate and zinc stearate are used as heat stabilizers to prevent PVC from degrading due to thermal decomposition during processing and use; calcium stearate can also act as a lubricant to improve processing performance. Nano calcium carbonate is a filler that can improve the hardness, strength and wear resistance of the material while reducing costs; the nano-scale particle size can make the surface of the material smoother and improve the filling property of the material. M50 isocyanate curing agent and aziridine crosslinking agent are used for curing reaction to transform PVC plastisol from liquid to solid, forming a three-dimensional network structure, improving the strength, hardness and chemical resistance of the material. Antioxidant 1010 and antioxidant 168 prevent PVC resin and other components from degradation due to oxidation during processing and use, extending the service life of the material. Silicone defoamer is used to eliminate bubbles generated during stirring and mixing, making the internal structure of the material denser and improving the quality and appearance of the material. Rutile titanium dioxide is a white pigment that provides good hiding power and whiteness, giving the material a better appearance; it can also improve the weather resistance and UV resistance of the material.
[0031] 2. Copal resin and biphenyl epoxy resin work together to build a more complex and tight cross-linked network. Copal resin provides flexibility and viscosity, so that the material will not be too brittle after curing; biphenyl epoxy resin enhances the degree of cross-linking, improves the hardness and wear resistance of the material. The combination of the two can make the PVC plastisol have good bonding strength and flexibility after curing, and have sufficient hardness, while improving the chemical corrosion resistance and water resistance of the material, and enhancing the comprehensive performance of the material.
[0032] 3. Shea butter and dioctyl maleate mainly provide flexibility, while PEG-10 distearate also has a plasticizing effect. They work together to weaken the interaction between PVC molecular chains, making the molecular chains easier to slide, thereby significantly improving the flexibility and ductility of the material. As a solubilizer and lubricant, isopropyl myristate can improve the compatibility between the components and make shea butter and PEG-10 distearate better dispersed in the PVC paste resin system. They cooperate with each other to make the entire system more uniform and stable, avoiding the phase separation phenomenon between the components. Shea butter and PEG-10 distearate can improve the compatibility between PVC paste resin, Copal resin and biphenyl epoxy resin, making the cross-linking reaction more uniform.
[0033] Shea butter contains some lipophilic groups that can interact with non-polar ingredients such as PVC paste resin; PEG-10 distearate has emulsifying and dispersing functions, and the hydrophilic and lipophilic parts in its molecular structure can help dissolve some ingredients with poor solubility in the system; isopropyl myristate itself is an excellent solubilizer. When they work together, they can reduce interfacial tension, allowing the originally difficult-to-dissolve ingredients to be better dispersed in the system. For some additives or pigments, they can encapsulate or disperse them, increase their solubility in PVC plastisol, thereby making the entire system more uniform and improving the quality and performance of the material.
[0034] Fourth, M50 isocyanate curing agent and aziridine crosslinking agent can cure PVC plastisol through different reaction mechanisms. Isocyanate group (-NCO) and aziridine group (-C3H5N) can react with PVC paste resin or other components containing active hydrogen to form a crosslinked structure. This dual-curing system can make the curing reaction more sufficient and form a denser three-dimensional network structure, thereby greatly improving the strength, hardness and chemical resistance of the material. At the same time, the reaction speeds of the two curing agents can be adjusted to each other, making the curing process more controllable and avoiding material performance defects caused by too fast or too slow curing. According to the specificity of other components, the present invention is designed to add a specific proportion of M50 isocyanate curing agent and aziridine crosslinking agent for use, which can ensure that the PVC plastisol is cured at low temperature in a short time and the curing quality is guaranteed.
[0035] 5. In S1 of the preparation method, the addition of dioctyl maleate, isopropyl myristate and PEG-10 distearate enables these plasticizers and solubilizers to better interact with the PVC paste resin to form a uniform basic glue. This process lays a good foundation for subsequent reactions and mixing, ensuring that each component can be evenly dispersed in the PVC paste resin.
[0036] 6. In S2 of the preparation method, adding shea butter first can achieve good fusion of Copal resin and biphenyl epoxy resin, and fuse with the base glue more quickly. Shea butter further plays a plasticizing role, and Copal resin and biphenyl epoxy resin begin to participate in the initial process of building a cross-linked network. Through long-term stirring, they are evenly mixed at the molecular level, preparing for the subsequent formation of a more complete cross-linked structure.
[0037] VII. In S4 of the preparation method, antioxidant 1010, antioxidant 168 and silicone defoamer are added. The temperature is lowered to accommodate the addition of antioxidants and to avoid the effects of excessively high temperatures on their performance. Antioxidants can effectively capture free radicals in the system at this stage to prevent oxidation reactions. The silicone defoamer can eliminate bubbles generated during the previous stirring process under low-speed stirring, making the system more compact. Subsequently, M50 isocyanate curing agent and aziridine crosslinking agent are added and stirred, so that the curing agent can fully react with the active ingredients in the system at a suitable temperature and stirring speed to form a crosslinked structure. DETAILED DESCRIPTION
[0038] The present invention is further described below in conjunction with specific implementation cases, but the present invention is not limited to these embodiments.
[0039] Example 1 A low-temperature baking type PVC plastisol comprises the following raw materials in parts by mass: 90 parts of PVC paste resin, 12 parts of Copal resin, 8 parts of biphenyl epoxy resin, 6 parts of shea butter, 30 parts of dioctyl maleate, 12 parts of isopropyl myristate, 4 parts of PEG-10 distearate, 3 parts of calcium stearate, 2 parts of zinc stearate, 15 parts of nano calcium carbonate, 2.5 parts of M50 isocyanate curing agent, 2 parts of aziridine crosslinking agent, 0.8 parts of antioxidant 1010, 0.8 parts of antioxidant 168, 0.2 parts of organosilicon defoaming agent, 4 parts of rutile titanium dioxide and 20 parts of ethyl acetate.
[0040] Among them, the PVC paste resin is a homopolymer resin with a polymerization degree of 1000; the particle size of calcium stearate is below 800 mesh sieve; the particle size of zinc stearate is below 650 mesh sieve; the particle size of nano calcium carbonate is below 100 nm; and the particle size of rutile titanium dioxide is below 425 mesh sieve.
[0041] The above-mentioned method for preparing a low-temperature baking type PVC plastisol comprises the following steps: S1: Add PVC paste resin to the reactor according to the mass fraction, stir at 400r / min, add dioctyl maleate, stir at 28°C for 18min, then add isopropyl myristate and PEG-10 distearate, stir for 40min, so that the PVC paste resin is fully swollen and mixed evenly to form a uniform base glue; S2: Add shea butter, copal resin and biphenyl epoxy resin pre-mixed with 85% by mass of ethyl acetate to the base glue according to the mass fraction, stir at a speed of 400 r / min for 15 min, and blend evenly; S3: Add calcium stearate, zinc stearate, nano calcium carbonate and rutile titanium dioxide according to their mass proportions, stir at 550 r / min for 25 min, and mix well; Calcium stearate, zinc stearate, nano calcium carbonate and rutile titanium dioxide are mixed evenly by air flow before being added; S4: Add antioxidant 1010, antioxidant 168 and silicone defoamer according to mass fractions, stir at 180r / min for 12min, let stand for 4min to allow bubbles to fully overflow, then add M50 isocyanate curing agent and aziridine crosslinking agent, stir at 220r / min for 40min, mix evenly and without bubble defects; S5: Finally, the remaining ethyl acetate was added, and the mixture was stirred at a speed of 200 r / min for 28 min to adjust the viscosity to obtain a PVC plastisol, which was sealed and stored.
[0042] In the above preparation method, the temperature does not exceed 32°C during the entire mixing process.
[0043] Example 2 A low-temperature baking type PVC plastisol comprises the following raw materials in parts by mass: 80 parts of PVC paste resin, 10 parts of Copal resin, 5 parts of biphenyl epoxy resin, 5 parts of shea butter, 25 parts of dioctyl maleate, 10 parts of isopropyl myristate, 3 parts of PEG-10 distearate, 2 parts of calcium stearate, 1 part of zinc stearate, 10 parts of nano calcium carbonate, 2 parts of M50 isocyanate curing agent, 1 part of aziridine crosslinking agent, 0.5 parts of antioxidant 1010, 0.5 parts of antioxidant 168, 0.1 parts of silicone defoaming agent, 3 parts of graphite powder and 15 parts of ethyl acetate.
[0044] Among them, the PVC paste resin is a homopolymer resin with a polymerization degree of 1000; the particle size of calcium stearate is below 900 mesh sieve; the particle size of zinc stearate is below 800 mesh sieve; the particle size of nano calcium carbonate is below 100nm; and the particle size of graphite powder is below 250 mesh sieve.
[0045] The above-mentioned method for preparing a low-temperature baking type PVC plastisol comprises the following steps: S1: Add PVC paste resin to the reactor according to the mass fraction, stir at 300 r / min, add dioctyl maleate, stir at 25°C for 15 min, then add isopropyl myristate and PEG-10 distearate, stir for 30 min, so that the PVC paste resin is fully swollen and mixed evenly to form a uniform base glue; S2: Add shea butter, Copal resin and biphenyl epoxy resin pre-mixed with 90% by mass of ethyl acetate to the base glue, and stir at 300 r / min for 10 min to blend evenly; S3: Add calcium stearate, zinc stearate, nano calcium carbonate and graphite powder according to their mass fractions, stir at 500 r / min for 20 min, and mix well; Calcium stearate, zinc stearate, nano calcium carbonate and graphite powder are mixed evenly by air flow before being added; S4: Add antioxidant 1010, antioxidant 168 and silicone defoamer according to mass fractions, stir at 150r / min for 10min, let stand for 3min to allow bubbles to fully overflow, then add M50 isocyanate curing agent and aziridine crosslinking agent, stir at 200r / min for 30min, mix evenly and without bubble defects; S5: Finally, the remaining ethyl acetate was added, and the mixture was stirred at a speed of 150 r / min for 25 min to adjust the viscosity to obtain a PVC plastisol, which was sealed and stored.
[0046] In the above preparation method, the temperature does not exceed 32°C during the entire mixing process.
[0047] Example 3 A low-temperature baking type PVC plastisol comprises the following raw materials in parts by mass: 80 parts of PVC paste resin, 15 parts of Copal resin, 5 parts of biphenyl epoxy resin, 8 parts of shea butter, 25 parts of dioctyl maleate, 15 parts of isopropyl myristate, 3 parts of PEG-10 distearate, 4 parts of calcium stearate, 1 part of zinc stearate, 20 parts of nano calcium carbonate, 2 parts of M50 isocyanate curing agent, 3 parts of aziridine crosslinking agent, 0.5 parts of antioxidant 1010, 1 part of antioxidant 168, 0.1 parts of silicone defoaming agent, 5 parts of pigment and 20 parts of ethyl acetate.
[0048] The PVC paste resin is a homopolymer resin with a polymerization degree of 1000; the particle size of calcium stearate is below 800 mesh sieve; the particle size of zinc stearate is below 800 mesh sieve; and the particle size of nano calcium carbonate is below 100 nm.
[0049] The pigment is a mixture of titanium dioxide and graphite powder in equal proportions; the titanium dioxide is rutile titanium dioxide with a particle size of passing through a 325-mesh sieve; and the graphite powder has a particle size of passing through a 325-mesh sieve.
[0050] The above-mentioned method for preparing a low-temperature baking type PVC plastisol comprises the following steps: S1: Add PVC paste resin to the reactor according to the mass fraction, stir at 300 r / min, add dioctyl maleate, stir at 26°C for 15 min, then add isopropyl myristate and PEG-10 distearate, stir for 30 min, so that the PVC paste resin is fully swollen and mixed evenly to form a uniform base glue; S2: Add shea butter, Copal resin and biphenyl epoxy resin pre-mixed with 85% by mass of ethyl acetate to the base glue, and stir at 500 r / min for 15 min to blend evenly; S3: Add calcium stearate, zinc stearate, nano calcium carbonate and pigment according to their mass fractions, stir at 500 r / min for 25 min, and mix evenly; Calcium stearate, zinc stearate, nano calcium carbonate and pigment are mixed evenly with double cone before adding; S4: Add antioxidant 1010, antioxidant 168 and silicone defoamer according to mass fractions, stir at 200 r / min for 10 min, let stand for 5 min to allow bubbles to fully overflow, then add M50 isocyanate curing agent and aziridine crosslinking agent, stir at 200 r / min for 45 min, mix evenly and without bubble defects; S5: Finally, the remaining ethyl acetate was added, and the mixture was stirred at a speed of 250 r / min for 25 min to adjust the viscosity to obtain a PVC plastisol, which was sealed and stored.
[0051] In the above preparation method, the temperature does not exceed 32°C during the entire mixing process.
[0052] Example 4 A low-temperature baking type PVC plastisol comprises the following raw materials in parts by mass: 100 parts of PVC paste resin, 15 parts of Copal resin, 10 parts of biphenyl epoxy resin, 8 parts of shea butter, 35 parts of dioctyl maleate, 15 parts of isopropyl myristate, 5 parts of PEG-10 distearate, 4 parts of calcium stearate, 3 parts of zinc stearate, 20 parts of nano calcium carbonate, 3 parts of M50 isocyanate curing agent, 3 parts of aziridine crosslinking agent, 1 part of antioxidant 1010, 1 part of antioxidant 168, 0.3 parts of organosilicon defoaming agent, 5 parts of rutile titanium dioxide and 25 parts of ethyl acetate.
[0053] Among them, the PVC paste resin is a homopolymer resin with a polymerization degree of 1000; the particle size of calcium stearate is below 900 mesh sieve; the particle size of zinc stearate is below 650 mesh sieve; the particle size of nano calcium carbonate is below 100 nm; and the particle size of rutile titanium dioxide is below 500 mesh sieve.
[0054] The above-mentioned method for preparing a low-temperature baking type PVC plastisol comprises the following steps: S1: Add PVC paste resin to the reactor according to the mass fraction, stir at 500r / min, add dioctyl maleate, stir at 30°C for 20min, then add isopropyl myristic acid and PEG-10 distearate, stir for 45min, so that the PVC paste resin is fully swollen and mixed evenly to form a uniform basic glue solution; S2: Add shea butter, Copal resin and biphenyl epoxy resin pre-mixed with 80% by mass of ethyl acetate to the base glue, and stir at a speed of 500 r / min for 20 min to blend evenly; S3: Add calcium stearate, zinc stearate, nano calcium carbonate and rutile titanium dioxide according to their mass proportions, stir at 600 r / min for 30 min, and mix evenly; Calcium stearate, zinc stearate, nano calcium carbonate and rutile titanium dioxide are mixed evenly with double cones before being added; S4: Add antioxidant 1010, antioxidant 168 and silicone defoamer according to mass fractions, stir at 200 r / min for 15 min, let stand for 5 min to allow bubbles to fully overflow, then add M50 isocyanate curing agent and aziridine crosslinking agent, stir at 250 r / min for 45 min, mix evenly and without bubble defects; S5: Finally, the remaining ethyl acetate was added, and the mixture was stirred at a speed of 250 r / min for 30 min to adjust the viscosity to obtain a PVC plastisol, which was sealed and stored.
[0055] In the above preparation method, the temperature does not exceed 32°C during the entire mixing process.
[0056] Example 5 A low-temperature baking type PVC plastisol comprises the following raw materials in parts by mass: 100 parts of PVC paste resin, 10 parts of Copal resin, 10 parts of biphenyl epoxy resin, 5 parts of shea butter, 35 parts of dioctyl maleate, 10 parts of isopropyl myristate, 5 parts of PEG-10 distearate, 2 parts of calcium stearate, 3 parts of zinc stearate, 10 parts of nano calcium carbonate, 3 parts of M50 isocyanate curing agent, 1 part of aziridine crosslinking agent, 1 part of antioxidant 1010, 0.5 parts of antioxidant 168, 0.3 parts of silicone defoaming agent, 3 parts of graphite powder and 20 parts of ethyl acetate.
[0057] Among them, the PVC paste resin is a homopolymer resin with a polymerization degree of 1200; the particle size of calcium stearate is below 800 mesh sieve; the particle size of zinc stearate is below 800 mesh sieve; the particle size of nano calcium carbonate is below 100nm; and the particle size of graphite powder is below 325 mesh sieve.
[0058] The above-mentioned method for preparing a low-temperature baking type PVC plastisol comprises the following steps: S1: Add PVC paste resin to the reactor according to the mass fraction, stir at 500r / min, add dioctyl maleate, stir at 32°C for 20min, then add isopropyl myristate and PEG-10 distearate, stir for 45min, so that the PVC paste resin is fully swollen and mixed evenly to form a uniform basic glue solution; S2: Add shea butter, Copal resin and biphenyl epoxy resin pre-mixed with 85% by mass of ethyl acetate to the base glue, and stir at 300 r / min for 20 min to blend evenly; S3: Add calcium stearate, zinc stearate, nano calcium carbonate and graphite powder according to their mass fractions, stir at 600 r / min for 20 min, and mix well; Calcium stearate, zinc stearate, nano calcium carbonate and graphite powder are mixed evenly by air flow before being added; S4: Add antioxidant 1010, antioxidant 168 and silicone defoamer according to mass fractions, stir at 150r / min for 15min, let stand for 3min to allow bubbles to fully overflow, then add M50 isocyanate curing agent and aziridine crosslinking agent, stir at 250r / min for 30min, mix evenly and without bubble defects; S5: Finally, the remaining ethyl acetate was added, and the mixture was stirred at a speed of 150 r / min for 30 min to adjust the viscosity to obtain a PVC plastisol, which was sealed and stored.
[0059] In the above preparation method, the temperature does not exceed 32°C during the entire mixing process.
[0060] Example 6 A low-temperature baking type PVC plastisol comprises the following raw materials in parts by mass: 95 parts of PVC paste resin, 11 parts of Copal resin, 9 parts of biphenyl epoxy resin, 6 parts of shea butter, 32 parts of dioctyl maleate, 12 parts of isopropyl myristate, 4 parts of PEG-10 distearate, 2 parts of calcium stearate, 2.5 parts of zinc stearate, 12 parts of nano calcium carbonate, 3 parts of M50 isocyanate curing agent, 1.5 parts of aziridine crosslinking agent, 0.8 parts of antioxidant 1010, 0.6 parts of antioxidant 168, 0.3 parts of silicone defoaming agent, 3 parts of pigment and 18 parts of ethyl acetate.
[0061] The PVC paste resin is a homopolymer resin with a polymerization degree of 1300; the particle size of calcium stearate is below 800 mesh sieve; the particle size of zinc stearate is below 800 mesh sieve; and the particle size of nano calcium carbonate is below 100 nm.
[0062] The pigment is a mixture of titanium dioxide and graphite powder in a mass ratio of 3:2; the titanium dioxide is rutile titanium dioxide, and the particle size is below 500 mesh sieve; the particle size of the graphite powder is below 200 mesh sieve.
[0063] The above-mentioned method for preparing a low-temperature baking type PVC plastisol comprises the following steps: S1: Add PVC paste resin to the reactor according to the mass fraction, stir at 350r / min, add dioctyl maleate, stir at 30°C for 20min, then add isopropyl myristic acid and PEG-10 distearate, stir for 30min, so that the PVC paste resin is fully swollen and mixed evenly to form a uniform basic glue solution; S2: Add shea butter, Copal resin and biphenyl epoxy resin pre-mixed with 90% by mass of ethyl acetate to the base glue according to the mass fraction, stir at a speed of 400 r / min for 10 min, and blend evenly; S3: Add calcium stearate, zinc stearate, nano calcium carbonate and pigment according to their mass fractions, stir at 600 r / min for 30 min, and mix evenly; Calcium stearate, zinc stearate, nano calcium carbonate and pigment are mixed evenly with double cone before adding; S4: Add antioxidant 1010, antioxidant 168 and silicone defoamer according to mass fractions, stir at 200 r / min for 15 min, let stand for 3 min to allow bubbles to fully overflow, then add M50 isocyanate curing agent and aziridine crosslinking agent, stir at 200 r / min for 40 min, mix evenly and without bubble defects; S5: Finally, the remaining ethyl acetate was added, and the mixture was stirred at a speed of 250 r / min for 30 min to adjust the viscosity to obtain a PVC plastisol, which was sealed and stored.
[0064] In the above preparation method, the temperature does not exceed 32°C during the entire mixing process.
[0065] The method for using the low-temperature baking type PVC plastisol prepared in the above embodiments is that the coating amount of the PVC plastisol is controlled at 120g / m² to 250g / m², and the baking temperature is controlled at 65°C to 80°C.
[0066] In the above embodiments: the model of PVC paste resin is PR-450, which is sourced from Yuyao Mingzhi Plastic Chemical Co., Ltd.; Kepa resin is sourced from Shenzhen Ruijit Biotechnology Co., Ltd.; the model of biphenyl epoxy resin is PA37346, which is sourced from Guangdong Wengjiang Chemical Reagent Co., Ltd.; shea butter is sourced from Guangzhou Jiaqi Biotechnology Co., Ltd.; the model of dioctyl maleate is DOM, which is sourced from Shandong Jingtai Chemical Co., Ltd.; the model of isopropyl myristate is IPM, which is sourced from Guangzhou Zhengli Chemical Co., Ltd.; PEG-10 distearate is sourced from Shanghai Huijun Chemical Co., Ltd.; calcium stearate is sourced from Dongguan Kangjin New Materials Technology Co., Ltd.; zinc stearate comes from Dongguan Kangjin New Materials Technology Co., Ltd.; nano calcium carbonate comes from Shanghai Naio Nano Technology Co., Ltd.; the model of M50 isocyanate curing agent is YN1828, which comes from Shanghai Kaizhi New Materials Technology Co., Ltd.; the model of aziridine cross-linking agent is HG-100, which comes from Guangzhou Hangeng New Materials Co., Ltd.; antioxidant 1010 comes from Dongguan Shanyi Plastic Co., Ltd.; antioxidant 168 comes from Dongguan Shanyi Plastic Co., Ltd.; the model of silicone defoamer is DP-217, which comes from Guangdong Tianfeng Defoamer Co., Ltd.; ethyl acetate comes from Shandong Hengshuo Chemical Co., Ltd.
[0067] Comparative Example 1 No Copal resin is added to the PVC plastisol, and the mass fraction of Copal resin is replaced by PVC paste resin; other parameters and methods are the same as in Example 1.
[0068] Comparative Example 2 No biphenyl epoxy resin is added to the PVC plastisol, and the mass fraction of the biphenyl epoxy resin is replaced by PVC paste resin; other parameters and methods are the same as in Example 1.
[0069] Comparative Example 3 No Copal resin and biphenyl epoxy resin are added to the PVC plastisol at the same time, and the mass fractions of Copal resin and biphenyl epoxy resin are replaced by PVC paste resin; other parameters and methods are the same as in Example 1.
[0070] Comparative Example 4 No shea butter was added to the PVC plastisol, and shea butter was replaced by 2 parts of ethyl acetate (to adjust the appropriate viscosity); other parameters and methods were the same as in Example 1.
[0071] Comparative Example 5 No isopropyl myristate was added to the PVC plastisol. The isopropyl myristate was prepared by 4 parts of ethyl acetate (to adjust the appropriate viscosity). Other parameters and methods were the same as those in Example 1.
[0072] Comparative Example 6 No PEG-10 distearate was added to the PVC plastisol, and PEG-10 distearate was replaced by 3 parts of ethyl acetate (to adjust the appropriate viscosity); other parameters and methods were the same as in Example 1.
[0073] Comparative Example 7 Neither shea butter nor PEG-10 distearate was added to the PVC plastisol. Shea butter and PEG-10 distearate were made from 5 parts of ethyl acetate (to adjust the appropriate viscosity). Other parameters and methods were the same as in Example 1.
[0074] Comparative Example 8 No shea butter, PEG-10 distearate and isopropyl myristate are added to the PVC plastisol. Shea butter, PEG-10 distearate and isopropyl myristate are made of 8 parts of ethyl acetate (to adjust the appropriate viscosity). Other parameters and methods are the same as in Example 1.
[0075] The properties of the PVC plastisols prepared in the above embodiments and comparative examples were tested.
[0076] 1. Test sample: 1. Material: A surface-treated aluminum alloy sheet with a thickness of 1mm and a size of 150mm×50mm is used. The aluminum alloy sheet is solid and has a smooth surface, and is not easily deformed during subsequent testing operations.
[0077] 2. Surface treatment: Use sandpaper to sand the aluminum alloy sheet until the surface roughness Ra is 0.8μm, and then use acetone to clean and degrease it to ensure that the surface of the steel sheet is clean and free of oil and impurities, enhance the adhesion between the PVC plastisol and the aluminum alloy sheet, and make the test results more reliable.
[0078] 2. Test items: 1. Initial viscosity: According to GB / T 2794 "Determination of viscosity of adhesives - Single cylinder rotational viscometer method", at a constant temperature of 25°C, take an appropriate amount of plastisol and place it in the measuring cylinder of the rotational viscometer, select a suitable rotor so that the reading is within the range of 30%-70%, rotate at 60r / min for 2 minutes, and then read the reading in mPa·s. The test results are shown in Table 1 below.
[0079] 2. Adhesion (bonding strength with substrate): Apply plastisol at 160g / m² to the sample, bake at 75℃ for 40min until solidified, use a grid knife to grid the solidified coating horizontally and vertically to form 100 1mm×1mm squares, stick the tape and compact it, then pull it up vertically quickly, observe the coating shedding rate in the squares, and evaluate it on a scale of 0-5, with 0 being the best. The test results are shown in Table 1 below.
[0080] 3. Water resistance (moisture resistance): Apply the plastisol at 160g / m² to the sample, bake at 75℃ for 40min until solidified, immerse the sample in 40℃ distilled water for 24h, 36h, 48h, 60h, 72h, then take it out and observe whether the coating has blistering, peeling, or discoloration, and record the time when the earliest obvious change occurs in hours. The test results are shown in Table 1 below.
[0081] 4. Shear strength: Prepare an aluminum alloy plate with a size of 100mm×25mm×2mm as the substrate, polish its surface with sandpaper to a roughness Ra of 1.6μm, then clean and degrease with acetone, and dry it for use. Apply low-temperature baking PVC plastisol evenly on the central area of an aluminum alloy plate, with a coating area of 20mm×25mm, and control the coating amount to 160g / m². Fit another aluminum alloy plate with the same treatment to it, ensuring that there are no bubbles or gaps, and fix it with a clamp with a clamp pressure of 0.5MPa. Leave it at room temperature for 24 hours, then bake the sample in a 75℃ oven until it solidifies, take it out and cool it to room temperature. Install the sample on the shear fixture of the universal material testing machine, make the force direction parallel to the glue layer, and load it uniformly at a speed of 5mm / min until the glue layer is destroyed, and record the maximum destructive load F (unit: N). Calculate shear strength =F / (20×25), unit: MPa. The test results are shown in Table 1 below.
[0082] 5. High temperature resistance: According to the sample preparation method for the shear strength test above, make multiple identical samples. Put the sample into a constant temperature oven with a set temperature, start from 80℃, increase the temperature by 5℃, and keep each temperature point for 2 hours. After the insulation is completed, take out the sample, cool it to room temperature, observe whether the adhesive layer has cracking, blistering, peeling, etc., and record the lowest temperature at which the sample is obviously damaged as the high temperature resistance limit. The test results are shown in Table 1 below.
[0083] 6. Low temperature resistance: Prepare the sample in the same way as the sample preparation process for shear strength test. Put the sample into the low temperature test chamber, start from -20℃, and gradually reduce the temperature by -5℃, and keep each temperature point for 2 hours. After the insulation is completed, take out the sample and observe the appearance to see if there are any cracks or brittleness. Record the lowest temperature at which the sample is obviously damaged as the low temperature resistance limit. The test results are shown in Table 1 below.
[0084] Table 1 Viscosity and performance test results
[0085] It can be seen from the above test results that the PVC plastisols of various embodiments have good bonding strength, water resistance, high and low temperature resistance, low baking temperature and fast curing speed.
[0086] From the test results of Comparative Example 1 (without adding Copal resin), it can be seen that Copal resin helps to increase the cohesion and viscosity of the system in the PVC plastisol system. Without Copal resin, the interaction of the system is weakened, resulting in a decrease in initial viscosity. Copal resin helps to enhance the bonding between the PVC plastisol and the substrate. Without Copal resin, the adhesion decreases and the bonding between the coating and the substrate becomes weaker. The tightness of the system deteriorates and water molecules are more likely to penetrate. Copal resin may help to enhance the interaction between molecules and the cross-linked structure in the system. Without Copal resin, the network structure of the glue after curing is not tight enough. When subjected to shear force, the molecular chains are prone to relative sliding, resulting in a decrease in shear strength. Copal resin helps to maintain the structural stability of the glue at high temperatures. Without Copal resin, the molecular chain movement of the glue is intensified at high temperatures. Due to insufficient cross-linking, cracking, blistering and other phenomena are more likely to occur, and the high temperature resistance limit is reduced. The absence of Copal resin reduces the flexibility and brittle crack resistance of the molecular chain of the glue at low temperatures. At low temperatures, the activity of the molecular chains is limited. Without sufficient cross-linking structure to buffer stress, the glue is more likely to become brittle and crack, and its low temperature resistance limit decreases.
[0087] From the test results of Comparative Example 2 (without adding biphenyl epoxy resin), it can be seen that biphenyl epoxy resin helps to promote the reaction of the system, improve the cross-linking viscosity, and has a positive effect on adhesion; without biphenyl epoxy resin, the interaction between the components of the system changes, the overall fluidity increases, and the adhesion decreases. Without biphenyl epoxy resin, the loose system structure makes it easier for water molecules to enter the coating, and the water resistance decreases. Biphenyl epoxy resin participates in the cross-linking reaction during the curing process to enhance the cohesion of the glue. In the absence of biphenyl epoxy resin, the degree of cross-linking is insufficient. When subjected to shear force, the bonding force inside the glue is weakened and the shear strength decreases. Biphenyl epoxy resin plays a key role in maintaining the structural integrity of the glue at high temperatures. Without biphenyl epoxy resin, the stability of the glue at high temperatures deteriorates, the force between the molecular chains is weakened, the temperature at which damage occurs is reduced, and the high temperature resistance limit decreases. In the absence of biphenyl epoxy resin, the rigidity of the molecular chain of the glue increases at low temperatures, and the flexibility deteriorates. In a low temperature environment, the glue cannot effectively resist the internal stress caused by the temperature reduction, and the low temperature resistance limit decreases.
[0088] From the test results of Comparative Example 3 (without adding Copal resin and biphenyl epoxy resin at the same time), it can be seen that both important resins are missing, the interaction of the system is severely damaged, and the viscosity is greatly reduced. The lack of both resins seriously reduces the bonding force between the coating and the substrate. Both resins are missing, the cross-linked network of the glue is severely damaged, and the interaction force between molecules is greatly weakened. Under the action of shear force, the glue has almost no enough cohesion to resist, and the shear strength is significantly reduced. The structural stability of the glue at high temperature is extremely poor. At high temperatures, the molecular chains of the glue are loose and cannot maintain their original form, and the high temperature resistance limit is greatly reduced. Without these two resins to adjust the flexibility and cohesion of the glue, the molecular chains become very fragile at low temperatures. In a low temperature environment, the glue is easily damaged by shrinkage and internal stress, and the low temperature resistance limit is reduced.
[0089] As can be seen from the test results of Comparative Example 4 (without adding shea butter), shea butter has a small effect on initial viscosity, and other main components still maintain their original interactions. Shea butter has a certain auxiliary effect on adhesion, plasticity, and solubility. Without shea butter, the fusion of other components is poor, the cross-linking effect is weakened, the adhesion is reduced to level 1, and the coating and substrate are weakened. Shea butter helps to form a waterproof barrier, and lacks shea butter, and the water resistance decreases. Shea butter plays a certain plasticizing and solubilizing effect on glue, enhances the lubricity between molecular chains, and enhances the fusion of resin components. Without shea butter, the friction between molecular chains increases, and under the action of shear force, the relative movement of molecular chains is hindered, and the shear strength decreases. Shea butter helps to maintain the flexibility of glue at high temperatures. Lack of shea butter, the flexibility of the molecular chain of glue at high temperatures is reduced, it is more likely to be damaged, and the high temperature limit decreases. The lack of shea butter weakens the mobility of the molecular chain of glue at low temperatures. In a low temperature environment, the glue is not flexible enough, the molecular chains are easily broken, and the low temperature resistance limit is reduced.
[0090] From the test results of Comparative Example 5 (without adding isopropyl myristate), it can be seen that isopropyl myristate has a solubilizing effect, improves the fusion of other ingredients, improves product uniformity, and then contributes to adhesion and water resistance. Without isopropyl myristate, adhesion and water resistance decrease. Isopropyl myristate helps the infiltration and adsorption of glue molecules on the surface of the adherend, thereby enhancing the bonding force. Without isopropyl myristate, the shear strength decreases. Isopropyl myristate improves the fusion of other ingredients, improves product uniformity, and has better stability of glue at high temperatures. In the absence of isopropyl myristate, the stability of glue at high temperatures is affected. In the absence of isopropyl myristate, the bonding force of glue with the substrate at low temperatures becomes weaker, and the flexibility of the glue itself is also reduced, and the low temperature resistance limit decreases.
[0091] From the test results of Comparative Example 6 (without adding PEG-10 distearate), it can be seen that PEG-10 distearate has a regulating effect on the viscosity of the system. PEG-10 distearate has a solubilizing effect, improves the fusion of other ingredients, improves the uniformity of the cross-linking reaction of the product, improves adhesion and water resistance, and without PEG-10 distearate, adhesion and water resistance deteriorate. PEG-10 distearate plays a role in regulating the cohesion and flexibility of the glue, as well as a solubilizing effect. Without PEG-10 distearate, the internal structure of the glue is uneven, and under the action of shear force, the force distribution of the molecular chain is unreasonable, and the shear strength decreases. PEG-10 distearate helps maintain the uniformity and stability of the glue at high temperatures. In the absence of PEG-10 distearate, the glue is prone to local structural damage at high temperatures, and the high temperature resistance limit decreases. In the absence of PEG-10 distearate, the flexibility and uniformity of the glue at low temperatures deteriorate. In a low temperature environment, the glue is prone to stress concentration due to uneven structure, and its low temperature resistance limit decreases.
[0092] The lack of two ingredients in Comparative Example 7 (no shea butter and PEG-10 distearate added at the same time) seriously deteriorates the system's fusion and uniformity, affects the system's cross-linking quality, and further greatly affects adhesion, shear strength, high temperature resistance and low temperature resistance.
[0093] The three solubilizing ingredients are missing at the same time in Comparative Example 8 (no shea butter, PEG-10 distearate and isopropyl myristate are added at the same time), which seriously affects the fusion of other ingredients, seriously deteriorates the uniformity, affects the uniformity of the cross-linking quality of the system, causes uneven internal stress, and greatly reduces the adhesion, shear strength, high temperature resistance and low temperature resistance.
Claims
1. A low-temperature baking type PVC plastisol, characterized in that: The PVC plastisol includes the following raw materials in parts by mass: 80 to 100 parts of PVC paste resin, 10 to 15 parts of Copal resin, 5 to 10 parts of biphenyl epoxy resin, 5 to 8 parts of shea butter, 25 to 35 parts of dioctyl maleate, 10 to 15 parts of isopropyl myristate, 3 to 5 parts of PEG-10 distearate, 2 to 4 parts of calcium stearate, 1 to 3 parts of zinc stearate, 10 to 20 parts of nano calcium carbonate, 2 to 3 parts of M50 isocyanate curing agent, 1 to 3 parts of aziridine crosslinking agent, 0.5 to 1 part of antioxidant 1010, 0.5 to 1 part of antioxidant 168, 0.1 to 0.3 parts of silicone defoaming agent, 3 to 5 parts of pigment and 15 to 25 parts of diluent.
2. A low-temperature baking type PVC plastisol according to claim 1, characterized in that: The PVC paste resin is a homopolymer resin with a polymerization degree of 1000-1300.
3. A low-temperature baking type PVC plastisol according to claim 1, characterized in that: The particle size of the calcium stearate is sieved through 800-900 mesh; the particle size of the zinc stearate is sieved through 650-800 mesh.
4. The low-temperature baking type PVC plastisol according to claim 1, characterized in that: The particle size of the nano calcium carbonate is less than 100 nm.
5. The low-temperature baking type PVC plastisol according to claim 1, characterized in that: The pigment is at least one of titanium dioxide and graphite powder; the titanium dioxide is rutile titanium dioxide, and the particle size of the titanium dioxide is 325-500 mesh sieve; the particle size of the graphite powder is 200-325 mesh sieve.
6. The low-temperature baking type PVC plastisol according to claim 1, characterized in that: The diluent is ethyl acetate.
7. A method for preparing a low-temperature baking type PVC plastisol, for preparing a low-temperature baking type PVC plastisol according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: S1: Add PVC paste resin to the reactor according to the mass fraction, stir at 300r / min~500r / min, add dioctyl maleate, stir at 25℃~32℃ for 15min~20min, then add isopropyl myristic acid and PEG-10 distearate, stir for 30min~45min, so that the PVC paste resin is fully swollen and mixed evenly to form a uniform basic glue solution; S2: Add 80% to 90% by mass of diluent, shea butter, Copal resin and biphenyl epoxy resin to the base glue solution, and stir at a speed of 300 r / min to 500 r / min to blend evenly; S3: Add calcium stearate, zinc stearate, nano calcium carbonate and pigment according to their mass fractions, stir at a speed of 500 r / min to 600 r / min, and mix evenly; S4: Add antioxidant 1010, antioxidant 168 and silicone defoamer according to their mass fractions, stir at a speed of 150r / min to 200r / min for 10min to 15min, let stand for 3min to 5min to allow bubbles to fully overflow, then add M50 isocyanate curing agent and aziridine crosslinking agent, stir at a speed of 200r / min to 250r / min, mix evenly and without bubble defects; S5: Finally, add the remaining diluent, stir at a speed of 150 r / min to 250 r / min, adjust the viscosity until it is uniform, and obtain PVC plastisol, which is sealed for storage.
8. The method for preparing a low-temperature baking type PVC plastisol according to claim 7, characterized in that: In S3, the calcium stearate, zinc stearate, nano calcium carbonate and pigment are uniformly mixed by double cone mixing or air flow mixing before being added.
9. The method for preparing a low-temperature baking type PVC plastisol according to claim 7, characterized in that: In S2, the stirring time at a speed of 300r / min to 500r / min is 10min to 20min; the shea butter, copal resin and biphenyl epoxy resin are pre-mixed with the diluent before being added; in S3, the stirring time at a speed of 500r / min to 600r / min is 20min to 30min; in S4, the stirring time at a speed of 200r / min to 250r / min is 30min to 45min; in S5, the stirring time at a speed of 150r / min to 250r / min is 25min to 30min.
10. A method for using a low-temperature baking type PVC plastisol, using the low-temperature baking type PVC plastisol according to any one of claims 1 to 6, characterized in that: The coating amount of PVC plastisol is controlled at 120g / m²~250g / m², and the baking temperature is controlled at 65℃~80℃.
Citation Information
Patent Citations
Adhesive composition
CA426532A
High-dispersibility modified calcium carbonate filler and preparation method thereof
CN104194400A
Tackifying type hot melt adhesive
CN108517189A